Shrine dedicated to the Goddess Annapurna - Mumbai Archive Project Team (Jio Institute, 2024)
A shrine dedicated to the goddess Annapurna (pictured), the provider of food and nourishment. Annapurna and other mother goddesses represent the primordial energy (Shakti) behind the universe's creation and the life force that sustains it.